Knight's Microsoft® Business Intelligence 24-Hour Trainer Leveraging Microsoft SQL Server® Integration, Analysis, and Reporti - Knight, Devin; Jorgensen, Adam; Leblanc, Patrick; Knight, Brian; Davis, Mike (Wrox, 2010)
Welcome to the video portion of Knight's Microsoft® Business Intelligence 24-Hour Trainer A book-and-video introduction to Microsoft's Business Intelligence tools If you are just starting to get a handle on Microsoft Business Intelligence (BI) tools, this book and accompanying video provides you with the just the right amount of information to perform basic business analysis and reporting. You'll explore the components and related tools that comprise the Microsoft BI toolset as well as the new BI features of Office 2010. After a basic primer on BI and data modeling, the expert team of authors provides you with step-by-step lessons in the book and videos on the accompanying Video on how to use SQL Server Integration Services, SQL Server Analysis Services, SQL Server Reporting Services, Excel BI (including PowerPivot), and SharePoint. Integrates instructional videos with each of the lessons found in the book to enhance your learning experience Explores the Microsoft Business Intelligence (BI) toolset as well as the new BI features of Office 2010 Encourages you to practice what you've learned in "Try It Out" sections Contains video demonstrations that walk you through how to tackle each lesson featured in the book With Knight's Microsoft Business Intelligence 24-Hour Trainer, veteran authors present you with an ideal introductory book-and-video package so that you can get started working with the BI toolset immediately!
Online resource; Title from title screen (viewed September 28, 2010)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos